Effectiveness of environmental surveillance of SARS-CoV-2 as an early warning system during the first year of the COVID-19 pandemic: a systematic review. (18th July 2022) - Hyllestad, Susanne; Myrmel, Mette; Lomba, Jose Antonio Baz; Jordhøy, Fredrik; Schipper, Svanhild Kjørsvik; Amato, Ettore
Abstract: Since infected persons shed SARS-CoV-2 in faeces before symptoms appear, environmental surveillance (ES) may serve as an early warning system (EWS) for COVID-19 and new variants of concern. The ES of SARS-CoV-2 has been widely reviewed; however, its effectiveness as an EWS for SARS-CoV-2 in terms of timeliness, sensitivity and specificity has not been systematically assessed. We conducted a systematic review to identify and synthesise evidence on the ES of SARS-CoV-2 as an EWS to evaluate the added value for public health. Of 1, 014 studies identified, we considered 29 for a qualitative synthesis of the timeliness of ES as an EWS for COVID-19, while six studies were assessed for the ability to detect new variants and two for both aims. The synthesis indicates ES may serve as an EWS of 1–2 weeks. ES could complement clinical surveillance for SARS-CoV-2; however, its cost–benefit value for public health decisions needs to be assessed based on the stage of the pandemic and resources available. Studies focusing methodological knowledge gaps as well as how to use and interpret ES signals for public health actions are needed, as is the sharing of knowledge within countries/areas with long experience of such surveillance. HIGHLIGHTS: Evidence on surveillance of SARS-CoV-2. Early warning system for COVID-19. Systematic review of environmental surveillance of SARS-CoV-2. Graphical Abstract